A Case Study: The Vicious Cycle of Headache, Uncontrolled Hypertension, and Paracetamol in 49 Years Old Woman: A Literature Review - Yudinda, Salsabilla Cathabell; Aulia Fahira (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Hypertension is a chronic condition that often presents without clear symptoms, but may cause complaints such as headaches. Many individuals with hypertension manage these symptoms independently using over-the-counter medications like paracetamol, without addressing the underlying cause. This case report aims to describe the clinical course of uncontrolled hypertension, recurrent headaches, and habitual paracetamol use. Case Illustration: A 49-year-old woman with a history of hypertension experienced recurrent headache and self-medicated with paracetamol without a prescription. The patient demonstrated poor adherence to antihypertensive therapy and maintained an unhealthy lifestyle, including frequent sleep deprivation, work-related stress, regular consumption of coffee, tea, and fried foods. Clinical evaluation revealed elevated blood pressure of 140/100 mmHg. Discussion: Non-adherence to antihypertensive treatment and unhealthy lifestyle choices were major contributing factors that exacerbated the patient’s condition. The use of paracetamol as a symptomatic treatment masked the underlying problem and poses long-term risks to organ function. Persistent headache may serve as a clinical indicator of uncontrolled blood pressure due to irregular therapy. Conclusion: Patients with hypertension require comprehensive management, including lifestyle modification, consistent adherence to medication, and education on the risks of self-medication. The use of symptomatic drugs such as paracetamol without medical supervision may worsen the condition if not accompanied by adequate blood pressure control.